When discrepant events change the plans: An unexpected investigation of physical properties and reactions. (2nd April 2016) - Madden, Lauren; Seifried, Joyce; Farnum, Kerry; D'Armiento, Angela
ABSTRACT: Discrepant events are often used by science educators to incite interest and excitement in learners, yet sometimes their results are farther-reaching. The following article describes how one such event—dissolving packing peanuts in acetone—led to a change in the course of a college-level elementary science teaching methods class and to the development of an inquiry-based lesson plan appropriate for use with fifth graders. The lesson is aligned to the NGSS ideas around helping children use observations of properties to describe materials and modeling scientific phenomena that are too small to observe with the naked eye.